KIAT-KIAT DALAM MENGHADAPI PENSIUN - Sudarilah, Sudarilah (MAJALAH ILMIAH WIDYA, 2012)
Retirement is new phase in life when employees have no work any longer for many reasons but most likely because they finishedtheir jobs untill they reach pension ages. The objective of this article is to discuss the retirement phase which can be prepared beforein order to avoid the misserable things.happen during the time. The method used library research and analized descriptively. It isconcluded that people need to have preparation for entering the retirement phase properly in their own ways economically, mentallyand phisically in order to avoid the phychologic effects, like post power syndrome.